Una tradición jurídica española: La autoridad paterna como el poder conjunto y solidario del padre y de la madre - Ureña y Smenjaud, Rafael de 1852-1930 (Dykinson, 2020)
A new edition of Rafael de Ureña y Smenjaud's (1852-1930) admission speech to the Real Academia de Ciencias Morales y Políticas (1912). "Una tradición jurídica española" studied the local charters or fueros of the Castilian-Aragonese Extremadura that consecrated the power over the children as a "joint and solidary" power of both the father and the mother; a legal rule in open contrast, according to the speaker, with the "Roman" solution of the criticized Spanish Civil Code. Based on the argument and the sources addressed in the speech, Carlos Petit's study examines Ureña's position in Spanish legal historiography, a speciality constituted as a discipline around his contemporary Eduardo de Hinojosa y Naveros (1852-1919), archivist and medievalist and mentor to some of the founders of the influential Anuario de Historia del Derecho Español (1924).
Keywords: Recht; Spanien; Law in general. Comparative and uniform law. Jurisprudence